Clinical characterization of acute and convalescent illness of confirmed chikungunya cases from Chiapas, S. Mexico: A cross sectional study - Roques, Pierre; Danis Lozano, Rogelio; Díaz González, Esteban Eduardo; Trujillo Murillo, Karina del Carmen; Caballero Sosa, Sandra; Sepúlveda Delgado, Jesús; Malo García, Iliana Rosalía; Canseco Ávila, Luis Miguel; Salgado Corsantes, Luis Manuel; Domínguez Arrevillaga, Sergio; Torres Zapata, Raúl; Gómez Cruz, Omar; et al. (2017)
Abstract Background The emerging chikungunya virus (CHIKV), is an arbovirus causing intense outbreaks in North America. The situation in Mexico is alarming, and CHIKV threatens to spread further throughout North America. Clinical and biological features of CHIKF outbreaks in Mexico have not been well described; thus, we conducted a cross sectional study of a CHIKV outbreak in Chiapas, Southern Mexico to further characterize these features. Methodology/Principal findings We collected blood samples from patients suspected of having chikungunya fever (CHIKF) who presented to Clinical Hospital ISSSTE Dr. Roberto Nettel in Tapachula, Chiapas, Mexico. In addition to the clinical examination, real-time polymerase chain reaction (PCR) standardized for the Asian Chikungunya lineage and/or enzyme-linked immunosorbent assay for immunoglobulin M (IgM) were used to confirm CHIKV diagnosis. Of a total of 850 patients who presented with probably CHIKV at Hospital “Dr. Roberto Nettel”, 112 probable CHIKF cases were enrolled in this study from November 2014- June 2015, of which 95 patients (84.8%) were CHIKV positive and 17 were negative (15.2%). Of these 95 CHIKV positive patients, 62 were positive by real-time reverse transcriptase PCR (+qRT-PCR); and 33 were seropositive to +IgM with a negative qRT-PCR. The most frequent symptoms reported were fever (100%), headache (82.3%), polyarthralgia (72.1%), and exanthem 82.3%). Biological abnormalities observed during CHIKV infection were lymphopenia (41.1%), leukopenia (51.6%), elevated transaminases (30.5%-46.3%) and high LDH (46.3%) and CRP (60.0%). Conclusion Clinical and biological data obtained from this study is providing more useful information for benchmarking purposes with outbreaks from different parts of the world and would be helpful for better patient care and treatment.